The Anesthetic Management of Complications during Obstetrical Emergencies - D, Barboza; Diouf E, Gaye I, Diop EN, Leye PA, Diaw M, Ndiaye PI,; Fall ML, Ba EB, Traoré M M, Bah MD, (International Journal of Innovative Research in Medical Science, 2017)
Anesthetic management of patients during obstetric emergencies is a serious problem, especially in developing countries. In daily practice, the anesthetist staff is confronted with many minor and major events which consequences can be benign or more serious. Our objective was to study the problem of the management of anesthetic complications during obstetric emergencies at the Ziguinchor Peace Hospital. We conducted a retrospective, descriptive and analytical study of all patients who underwent surgical intervention in the operating room during obstetric surgical emergencies. During this study period 325 patients were operated on. Age was reported in 323 files. The average age was 27.2 years old. Hypotension and hemorrhagic shock were the main complications. The timing of complications was 53.1% at induction and 46.9% at upkeep. The average hemoglobin level and the average platelet count were lower in women who had complications than those who did not. The immediate evolution was often good. All cases of death (2%) were related to hemorrhagic shock often associated with disseminated intravascular coagulopathy that can not be managed by the unavailability of fresh frozen plasma, platelet concentrates and other coagulation products.